Spring foraging movements of an urban population of grey-headed flying foxes (Pteropus poliocephalus). Issue 1 (22nd January 2021) - Boardman, Wayne S J; Roshier, David; Reardon, Terry; Burbidge, Kathryn; McKeown, Adam; Westcott, David A; Caraguel, Charles G B; Prowse, Thomas A A
Abstract: Flying foxes provide ecologically and economically important ecosystem services but extensive clearing and modification of habitat and drought combined with the planting of commercial and non-commercial trees across various landscapes, has meant flying foxes in Australia are increasingly seeking foraging resources in new areas. In 2011, grey-headed flying foxes formed a camp in Adelaide, South Australia, outside their previously recorded range. We used global positioning system telemetry to study the movements and foraging behaviour of this species in Adelaide in spring (September to November) 2015. High-frequency location data were used to determine the foraging range and the most frequently visited foraging sites used by each bat which were ground-truthed to identify forage plants. A total of 7239 valid locations were collected over 170 nights from four collars. Despite being a highly mobile species, the mean core foraging range estimate was only 7.30 km 2 (range 3.3–11.2 km 2 ). Maximum foraging distance from the camp in the Botanic Park was 9.5 km but most foraging occurred within a 4-km radius. The most common foraging sites occurred within the residential area of Adelaide and included introduced forage plant species, Lemon-scented gum ( Corymbia citriodora ) and Port Jackson fig ( Ficus rubiginosa ). Other observed movement activities included dipping behaviour on inland and marine waters and travel across flight paths around Adelaide airport. Our findings suggest that urban habitats in Adelaide provide sufficient foraging resources for grey-headed flying foxes to use these areas exclusively, at least in spring. This creates substantial opportunities for bats to interact with humans and their infrastructure.